2013
DOI: 10.1155/2013/189464
|View full text |Cite
|
Sign up to set email alerts
|

Mg(II) Selective PVC Membrane Electrode Based on Methyl Phenyl Semicarbazone as an Ionophore

Abstract: A PVC-membrane-based Mg(II) selective electrode was constructed using methyl phenyl semicarbazone (MPS) as a neutral carrier. The sensor exhibits a Nernstian response for Mg(II) ion over a wide concentration range1.0×10-8  to  1.0×10-1 M with the slope of 28.4 mV/per decade having detection limit1.7×10-9 M. It was relatively a fast response time (<10 s for concentration≥1.0×10-3and<15 s for concentration of≥1.0×10-6 M) and can be used for 8 months without any considerable divergence in potentials. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Some of the challenges in elucidation the nature and extent of the binding of Mg 2+ by NOM are associated with the limitations of methods available for probing these interactions, preferably at environmentally relevant concentrations of Mg 2+ and NOM. As opposed to the extensive data obtained using Ca 2+ -selective electrodes (ISE), Mg 2+ –specific ISE have not been successfully used to examine NOM–Mg 2+ interactions, apparently due to the limitations of their performance. Stability constants derived to account for Mg 2+ -complexation in geochemical models, for example, NICA–Donnan Model and Model V have been derived via the analysis of the acid–base titration curves generated in the absence and presence of MgCl 2 . , These and related experiments were carried out using solutions in which the concentrations of Mg 2+ and humic substances were several orders of magnitude higher than those in environmental systems. The data obtained in these studies for Mg 2+ –NOM interactions are limited, and the model parameters suggested in prior research remain largely untested. …”
Section: Introductionmentioning
confidence: 99%
“…Some of the challenges in elucidation the nature and extent of the binding of Mg 2+ by NOM are associated with the limitations of methods available for probing these interactions, preferably at environmentally relevant concentrations of Mg 2+ and NOM. As opposed to the extensive data obtained using Ca 2+ -selective electrodes (ISE), Mg 2+ –specific ISE have not been successfully used to examine NOM–Mg 2+ interactions, apparently due to the limitations of their performance. Stability constants derived to account for Mg 2+ -complexation in geochemical models, for example, NICA–Donnan Model and Model V have been derived via the analysis of the acid–base titration curves generated in the absence and presence of MgCl 2 . , These and related experiments were carried out using solutions in which the concentrations of Mg 2+ and humic substances were several orders of magnitude higher than those in environmental systems. The data obtained in these studies for Mg 2+ –NOM interactions are limited, and the model parameters suggested in prior research remain largely untested. …”
Section: Introductionmentioning
confidence: 99%
“…After immersing the prepared sensor and the reference sensor in 1*10 -6 and 1*10 -2 M of MFN solution, the proposed electrodes attained stable potentials after 0.7, 1.5, and 1.3 minutes at 1*10 -2 M and after 3.2, 3.6, and 5.8 minutes at (1*10 -6 M) for electrodes A, B, and C, respectively. The results were represented in Figures (9)(10)(11). The lifetime of the three electrodes were measured and found that it was 17, 39 and 12 day for electrode A, B and C, respectively.…”
Section: Response Time and Lifetimementioning
confidence: 99%
“…The (MFN-BPB) ionfore was prepared by stirring together 100 mL of a 0.01M solution of MFN and 100 mL of a 0.01 M solution of BPB. The formed precipitate was further filtered, rinsed with millipore water, and dried at 60 o C. 10 Preparation of Sensor Davis et al 11 report the hardening process of moxifloxacin into the matrix sensor. Add 0.040 g of the complex, 0.360 g of plasticizer, and 0.17 g of polyvinyl chloride as support, then add 7 mL of tetra hydro furan with stirring until the formation of the viscous solution.…”
Section: Synthesis Of Ion Pairmentioning
confidence: 99%
“…ISEs with neutral carrier-based polymeric membranes have been in development for decades [8,9]. Many different ion sensors have been reported [10][11][12]. However, most carbonate-selective electrodes are of the traditional inner-liquid-electrolyte variety, and are inconvenient and non-portable.…”
Section: Introductionmentioning
confidence: 99%